Effect of Tensile Reinforcement Ratio on the Effective Moment of Inertia of Reinforced Lightweight Concrete Beams for Short Term Deflection Calculation - Akmaluddin Akmaluddin (Institute for Research and Community Services, Institut Teknologi Bandung, 2011)
This paper presents an improvement model of the effective moment of inertia to predict the short term deflection of reinforced lightweight concrete beam. The models were developed using 9 beams of reinforced pumicelightweight concrete tested under two symmetrical-point loads. The presence of steel reinforcement in the beam was taken into consideration in the developed model. The models were verified by test carried out on other 9 beams. Those beams subjected to various-point loads and compressive strength. The results of investigation revealed that crack moment of inertia increased with the increased tensile reinforcement ratio. Thus, the reinforcement ratio significantly affects the value of effective moment of inertia of reinforced lightweight concrete beam. All the beam test results produced considerable deflection in comparison to that obtained using current Codes either ACI or SNI. The proposed model demonstrated a good agreement to the experimental results and in some cases have similar trend to that of the ACI or SNI prediction.